Sagittale Gelenkinstabilität im kreuzbandinsuffizienten kaninen Kniegelenk - Rey, J.; Fischer, M. S.; Böttcher, P. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: This in vivo study qualitatively describes the sagittal motion pattern of the cranial cruciate ligament (CrCL) insufficient canine stifle in operated and unoperated joints with cranio-caudal laxity on palpation. Material and methods: Sagittal stifle kinematics were recorded in vivo in dogs (> 15 kg BW) with unilateral (n = 7) or bilateral (n = 6) complete CrCL rupture and positive cranial drawer test as well as two sound control dogs using uniplanar fluoroscopic kinematography with the dogs walking on a treadmill. Stifle stability and sagittal motion pattern of the femur and the tibia were determined by visual inspection of the fluoroscopic video sequences. Results: Control dogs showed no cranio-caudal instability, identical to the contralateral stifles of the dogs with unilateral rupture. All unoperated stifles with CrCL rupture (n = 6) showed caudal slippage of the femur at the beginning of the stance phase. Of the 13 operated stifles (TightRope: n = 1, tibial tuberosity advancement, TTA: n = 6, tibial plateau leveling osteotomy, TPLO: n = 5, cranial closing wedge osteotomy, CCWO: n = 1) nine were unstable, showing the same motion pattern as the unoperated stifles. Conclusion: In the CrCL insufficient stifle with in vivo cranio-caudal instability caudal slippage of the distal femur at tow touch is the predominant motion pattern. Clinical significance: The discrepancy between in vivo motion pattern and in vitro simulation of CrCL insufficiency in which cranial tibial subluxation is the predominant sagittal motion pattern warrants further studies.
Keywords: Key words Stifle; cranial cruciate ligament rupture; in vivo; kinematics; fluoroscopy